Biomechanics gait analysis of women with mammary hypertrophy Análisis de la biomecánica de la marcha en mujeres con hipertrofia mamaria - Schutz G.R.* (2013)
Mammary hypertrophy is an abnormal increase of breasts, resulting in women several adaptations, such as changes in gait and balance. Our objective is to analyze the kinematic and kinetic characteristics of gait in women with mammary hypertrophy. Thirteen women with mammary hypertrophy took part of this study. A force plate was used to measure the vertical component of gait. The variables analysed were: first peak of force (FPF), second peak of force (SPF), weight acceptance rate (WAR) mid-stance (MS). Two video cameras (30 Hz) were used for kinematic analysis. The following spatio-temporal variables were analyzed: SLS (single support time right and left), DLS (double support time), ST (stride time), ScT (stance time) SwT (swing time), SL (step length right and left), SdL (stride length), SW (stride width) and v (velocity). The kinetic variables FPF, SPF and WAR and the spatio-temporal variables DLS, ScT, SwT, SL, SdL, SW and v showed different values when compared with normal women in same-age. The women walk more slowly, with small step length and a greater stride width, which generates greater weight acceptance period with the flat foot in the early support. It can be conclude that the gait of women with mammary hypertrophy has different characteristics from biomechanical standard in healthy women in same-age, similar with characteristics of obese women. © 2014 Sociedad Española de Cirugía Plástica, Reparadora y Estética (SECPRE).